A promising novel strain of L. reuteri DSM20016 as a chassis for synthetic biology applications - Duggan, Alexander D.; Dillon, Marcus M.; McMillen, David R. (Frontiers in Synthetic Biology, 2025)
Limosilactobacillusreuteri strain DSM 20016 is specialised to colonize the human gut for much longer than other L. reuteri strains and most other Lactobacillaceae family members. These adaptations, along with its safe-to-consume food status and public acceptance as a probiotic, make it an attractive chassis for synthetic biology endeavours aimed at introducing novel functions into the gut microbiome, including feedback systems for sensing disease state and therapeutic applications for remedying chronic disorders. Here, we perform whole-genome sequencing and present a novel variant of L. reuteri DSM 20016 (now denoted “LAD4” in this work; DSMZ repository number 116333) with mutations that disrupt DNA restriction-modification and cell wall regulation; these appear to enable increased uptake of the PAMβ1-origin low copy-number plasmid pTRKH3. Additional mutations include genes involved in protein degradation ability, alkaline shock responses, and a mobile genetic element transfer. One of these mutations, or some combination of them, enables stable, consistent production and detection, without the need to buffer media, of the acid-resistant reporter protein mCherry2. This novel variant, in combination with the pTRKH3 plasmid backbone, will enable researchers to more easily utilize this uniquely positioned microbe, which was previously limited by inconsistent reporter protein production and unreliable growth characteristics.